Method of estimation of synchronization strength between low-frequency oscillations in heart rate variability and photoplethysmographic waveform variability - Anton R. Kiselev; Anatoly S. Karavaev; Vladimir I. Gridnev; Mikhail D. Prokhorov; Vladimir I. Ponomarenko; Ekaterina I. Borovkova; Vladimir A. Shvartz; Yurii M. Ishbulatov; Olga M. Posnenkova; Boris P. Bezruchko (Russian Open Medical Journal, 2016)
This paper describes in detail a new method proposed by authors for quantitative estimation of the strength of synchronization between the low-frequency oscillations (with the main frequency of about 0.1 Hz) in the heart rate variability (HRV) and photoplethysmogram (PPG). Calculation of index value is followed by statistical significance control. The proposed method is applied for the analysis of 1056 pairs of HRV and PPG signals obtained from patients having different clinical status. Methodological recommendations are developed for method application in clinical studies.